MODEL BIMBINGAN KELOMPOK BERBASIS NILAI NENGAH NYAMPUR DALAM FALSAFAH HIDUP MASYARAKAT LAMPUNG UNTUK MENINGKATKAN PENYESUAIAN DIRI SISWA - Rosidah, Ainur; Nurfaizal, Nurfaizal; Fitria, Nita (JURNAL FOKUS KONSELING, 2015)
AbstractÂ Self adjusment being a major capital hearts facing the challenges of life are fluctuating. Self adjustment problems in this research will be enhanced through the provision of group counseling services based the value "nengah nyampur" in the philosophy of life Lampung people. This study aims to determine the effectiveness of the review the provision of the model of group counseling services based the value "nengah nyampur" in the philosophy of life Lampung people to increases self adjustment studentsâ in the first grade of the MTs Al Falah Sinar Gunung. The methods of the research is a research and development (R & D). The result of the research shows that the self adjustment studentsâ in the first grade of Mts Al Falah Sinar Gunung increased significantly. This increase is characterized by the average value of studentsâ data pre-test and post-test in experimental group, the average value on the pre-test of 94.6 and average value on the post-test of 144.3. So that the average value increased by 49.7. Thus, the model of group counseling services based the value ânengah nyampurâ in the philosophy of life Lampung people effective to improve self adjusment studentsâ.Â Â Keywods:group counseling service based the value ânengah nyampurâ, philosophy of life, self adjusment